Exploring Other-Than-Human Identity: A Narrative Approach to Otherkin, Therianthropes, and Vampires - Baldwin, Clive; Ripley, Lauren (Qualitative Sociology Review, 2020)
Drawing on in-depth, narrative interviews with 24 self-identified Otherkin, Therianthropes, and Vampires, we explore how members of these communities navigate Bamberg’s three “dilemmatic spaces” or tensions of continuity/change, similarity/difference, and person-to-world/world-to-person fit. With regard to the first, we identify four aetiological narratives (walk-ins, reincarnation, trapped soul, and evolutionary soul), and discuss stories of shifts and awakening. For the second, we discuss how participants manage the similarity/difference tension with regard to themselves and humans, and explore categorical and renunciatory othering within the communities. Finally, we explore the ways in which members of the communities experience a barren narrative environment, and ways they seek to construct storyworlds and narrative resources as frames for establishing their identities.